Evaluation of endoscopic ultrasound fine-needle aspiration versus fine-needle biopsy and impact of rapid on-site evaluation for pancreatic masses - de Moura, Diogo T.H.; McCarty, Thomas R.; Jirapinyo, Pichamol; Ribeiro, Igor B.; Hathorn, Kelly E.; Madruga-Neto, Antonio Coutinho; Lee, Linda S.; Thompson, Christopher C. (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) is traditionally considered a first-line strategy for diagnosing pancreatic lesions; however, given less than ideal accuracy rates, fine-needle biopsy (FNB) has been recently developed to yield histological tissue. The aim of this study was to compare diagnostic yield and safety between EUS-FNA and EUS-FNB in sampling of pancreatic masses.Patients and methods This was a multicenter retrospective study to evaluate efficacy and safety of EUS-FNA and EUS-FNB for pancreatic lesions. Baseline characteristics including sensitivity, specificity, and accuracy, were evaluated. Rapid on-site evaluation (ROSE) diagnostic adequacy, cell-block accuracy, and adverse events were analyzed. Subgroup analyses comparing FNA versus FNB route of tissue acquisition and comparison between methods with or without ROSE were performed. Multivariable logistic regression was also performed.Results A total of 574 patients (n = 194 FNA, n = 380 FNB) were included. Overall sensitivity, specificity, and accuracy of FNB versus FNA were similar [(89.09 % versus 85.62 %; P = 0.229), (98.04 % versus 96.88 %; P = 0.387), and 90.29 % versus 87.50 %; P = 0.307)]. Number of passes for ROSE adequacy and cell-block accuracy were comparable for FNA versus FNB [(3.06 ± 1.62 versus 3.04 ± 1.88; P = 0.11) and (3.08 ± 1.63 versus 3.35 ± 2.02; P = 0.137)]. FNA + ROSE was superior to FNA alone regarding sensitivity and accuracy [91.96 % versus 70.83 %; P < 0.001) and (91.80 % versus 80.28 %; P = 0.020)]. Sensitivity of FNB + ROSE and FNB alone were superior to FNA alone [(92.17 % versus 70.83 %; P < 0.001) and (87.44 % versus 70.83 %; P < 0.001)]. There was no difference in sensitivity though improved accuracy between FNA + ROSE versus FNB alone [(91.96 % versus 87.44 %; P = 0.193) and (91.80 % versus 80.72 %; P = 0.006)]. FNB + ROSE was more accurate than FNA + ROSE (93.13 % versus 91.80 %; P = 0.001). Multivariate analysis showed ROSE was a significant predictor of accuracy [OR 2.60 (95 % CI, 1.41–4.79)]. One adverse event occurred after FNB resulting in patient death.Conclusion EUS-FNB allowed for more consistent cell-block evaluation as compared to EUS-FNA. EUS-FNA + ROSE was found to have a similar sensitivity to EUS-FNB alone suggesting a reduced need for ROSE as part of the standard algorithm of pancreatic sampling. While FNB alone produced similar diagnostic findings to EUS-FNA + ROSE, FNB + ROSE still was noted to increase diagnostic yield. This finding may favor a unique role for FNB + ROSE, suggesting it may be useful in cases when previous EUS-guided sampling may have been indeterminate.